Risk perceptions, worry, and attitudes about genetic testing for breast cancer susceptibility. - Cameron LD; Reeve J (Psychology & Health, 2006)
This study assessed the unique associations of risk perceptions and worry with attitudes about genetic testing for breast cancer susceptibility. Women (general practitioner clinic attenders, university students, and first-degree relatives of breast cancer survivors; N=303) read information about genetic testing and completed measures assessing perceived cancer risk, cancer worry, and genetic testing attitudes and beliefs. Worry was associated with greater interest in genetic testing, stronger beliefs that testing has detrimental emotional consequences, and positive beliefs about benefits of testing and risk-reducing surgeries. Perceived risk was unrelated to interest and associated with more skeptical beliefs about emotional consequences and benefits of testing and risk-reducing surgeries. At low worry levels, testing interest increased with more positive beliefs about testing benefits; at high worry levels, interest was high regardless of benefits beliefs. The findings support Leventhal's Common-Sense Model of self-regulation delineating interactive influences of risk-related cognitions and emotions on information processing and behavior.